Relevansi Konsep Harta Isti’mali dalam Ekonomi Islam Kontemporer - Nadina Putri; Nur Azizah; Intan Syarifah (Economia: Journal of Economics and Management, 2026)
This article examines the relevance of the concept of harta isti’mali in contemporary Islamic economics as a normative framework for individual wealth management. Harta isti’mali is understood as wealth owned to fulfill personal and household needs, rather than for commercial or profit-oriented productive activities. This study employs a qualitative approach with a normative-conceptual library research design, based on the analysis of classical fiqh sources, contemporary Islamic economic thought, and relevant academic literature. The findings indicate that the classification of wealth in Islam is not determined by the physical form of assets, but by their function, purpose of use, and orientation of utilization. In the context of modern economic life, the blurring of boundaries between needs and desires, as well as the transformation of asset functions, generates significant ethical and legal implications, particularly in relation to consumption ethics and zakat obligations. The concept of harta isti’mali plays a strategic role as an ethical instrument in shaping moderate, just, and sustainable Islamic economic practices. The revitalization of this concept is essential to align Muslim economic behavior with the objectives of maqasid al-shariah in responding to contemporary economic dynamics. Abstrak Artikel ini mengkaji relevansi konsep harta isti’mali dalam konteks ekonomi Islam kontemporer sebagai kerangka normatif dalam pengelolaan kekayaan individu. Harta isti’mali dipahami sebagai harta yang dimiliki untuk memenuhi kebutuhan pribadi dan rumah tangga, bukan untuk tujuan komersial atau aktivitas produktif. Penelitian ini menggunakan pendekatan kualitatif dengan desain penelitian kepustakaan (library research) yang bersifat normatif-konseptual, melalui analisis terhadap sumber-sumber fikih klasik, pemikiran ekonomi Islam kontemporer, serta literatur akademik yang relevan. Hasil kajian menunjukkan bahwa klasifikasi harta dalam Islam tidak ditentukan oleh bentuk fisik aset, melainkan oleh fungsi, tujuan pemanfaatan, dan orientasi penggunaannya. Dalam konteks ekonomi modern, kaburnya batas antara kebutuhan dan keinginan serta perubahan fungsi harta menimbulkan implikasi etis dan hukum, khususnya terkait etika konsumsi dan kewajiban zakat. Konsep harta isti’mali memiliki peran strategis sebagai instrumen etis untuk membangun praktik ekonomi Islam yang moderat, berkeadilan, dan berkelanjutan. Revitalisasi konsep ini penting untuk menyelaraskan perilaku ekonomi individu Muslim dengan tujuan maqasid al-shariah dalam menghadapi dinamika ekonomi kontemporer.